Experiential Learning as a Strategy for Student Completion and Course Success in the Community College. Issue 10 (2nd November 2019) - Walker, Carolyn
ABSTRACT: Community college leaders seeking best practices to improve completion rates and student success have a strategy to consider – experiential learning as part of a course. An accounting business course, at a mid-sized community college in the southeast, recently implemented an experiential learning activity to determine the association with students obtaining a degree and completing a course successfully. A comparison of graduation rates and end-of-course grades, between experiential and non-experiential learning participants, yielded positive benefits for the experiential learning participants.